PENGEMBANGAN MEDIA PEMBELAJARAN KARSISTEM BERBASIS QR-CODE GUNA MENINGKATKAN PEMAHAMAN KONSEP EKOSISTEM PADA SISWA KELAS V SD MUHAMMADIYAH 11 SEMARANG - Noval Lail Aditya (CV. KAMPUS AKADEMIK PUBLISHING, 2024)
Development of KARSISTEM Learning Media (Ecosystem Cards) Based on QR-Code to Enhance Concept Understanding of Grade V Students at Muhammadiyah 11 Semarang” The background of this research is based on interviews with the fifth-grade teacher, revealing that students show low enthusiasm during IPAS lessons because the teacher primarily uses textbooks. Additionally, the teacher rarely utilizes learning media, often relying on a lecture method for material explanation, which causes student boredom. During the learning process, students are allowed to use their mobile phones to support classroom learning. The aims of this research are to develop QR-Code based learning media called